East African agriculture and climate change: A comprehensive analysis - Uganda - Bashaasha, Bernard; Thomas, Timothy S.; Waithaka, Michael; Kyotalimye, Miriam (International Food Policy Research Institute, 2012)
This summary note is an excerpt from the chapter on Uganda that will appear in the peer-reviewed IFPRI monograph, East African Agriculture and Climate Change: A Comprehensive Analysis.